1997
DOI: 10.1164/ajrccm.156.3.9608049
|View full text |Cite
|
Sign up to set email alerts
|

Concealed Air Leak Associated with Large Tidal Volumes in Partial Liquid Ventilation

Abstract: Current ventilator strategies aim at maintaining an open lung and limiting both peak inspiratory pressures and tidal volumes to avoid alveolar distension. Perfluorocarbons, as well as being excellent solvents for oxygen and carbon dioxide, have the unique properties of being able to recruit dependent lung regions and improve pulmonary mechanics. Optimal ventilator strategies for partial liquid ventilation (PLV) have not yet been clearly defined. In the surfactant-depleted rabbit model, an approach involving a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 28 publications
2
23
0
1
Order By: Relevance
“…Recent studies indicate that improvement in pulmonary gas exchange and mechanics and reduction in barotrauma during PLV is favored by surfactant pretreatment, higher PFC doses, higher breathing frequencies (within the conventional range), and smaller tidal volumes to prevent overdistension, optimize PFC distribution, and minimize exposure of the alveolarcapillary membrane to a gas-liquid interface. [128][129][130]132 Maintenance of a therapeutic PFC liquid volume following initial instillation in the lungs is dependent on the rate of PFC elimination during gas ventilation, which is influenced by many factors, including time, PFC physical properties, gas to liquid contact, ventilation strategy, lung pathophysiology, repositioning of the subject, and the administration of supplemental PFC doses to the lungs (see Uptake, Biodistribution, and Elimination of PFC During LAV). Lung protection is enhanced by replacing PFC liquid at the measured loss rate.…”
Section: Partial Liquid Ventilation Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies indicate that improvement in pulmonary gas exchange and mechanics and reduction in barotrauma during PLV is favored by surfactant pretreatment, higher PFC doses, higher breathing frequencies (within the conventional range), and smaller tidal volumes to prevent overdistension, optimize PFC distribution, and minimize exposure of the alveolarcapillary membrane to a gas-liquid interface. [128][129][130]132 Maintenance of a therapeutic PFC liquid volume following initial instillation in the lungs is dependent on the rate of PFC elimination during gas ventilation, which is influenced by many factors, including time, PFC physical properties, gas to liquid contact, ventilation strategy, lung pathophysiology, repositioning of the subject, and the administration of supplemental PFC doses to the lungs (see Uptake, Biodistribution, and Elimination of PFC During LAV). Lung protection is enhanced by replacing PFC liquid at the measured loss rate.…”
Section: Partial Liquid Ventilation Techniquementioning
confidence: 99%
“…During this time, preclinical studies have indicated that frequencies within the conventional range can be maintained during instillation and barotrauma is significantly reduced when using low pressures and low tidal volumes and high-frequency strategies. 128,132 Clinical information to date is inconclusive. However, we experienced that 1) inspiratory pressures may need to be decreased to avoid overdistention as lung compliance improves; 2) expiratory pressures may need to be increased to facilitate distal migration of the liquid into the lung; and 3) inspired oxygen may need to be increased briefly to overcome initial diffusional limitations associated with a liquid respiratory medium.…”
Section: Clinical Care During Partial Liquid Ventilationmentioning
confidence: 99%
See 1 more Smart Citation
“…Overdosing of PFC may increase the risk of pneumothorax because of the static pressure of PFC and high MAP [29] . Baden et al [30] reported that a larger volume of PFC (30 ml/kg) did not produce marked improvements in oxygenation in a piglet model of ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Current ventilator strategies in PLV have tended to use larger tidal volumes and near FRC doses of PFB, with the recommendation of at least a low level of PEEP (5 cm H 2 O) to avoid the high airway pressures caused by slow moving liquid in central airways [8]. Recently, Cox et al [13] reported a significant risk of barotrauma in a surfactant-depleted rabbit model in which a large tidal volume (15 ml/kg) was used in association with a lung filled to FRC with PFB.…”
Section: Discussionmentioning
confidence: 99%